HACD1 , a regulator of membrane composition and fluidity, promotes myoblast fusion and skeletal muscle growth - Blondelle, Jordan; Ohno, Yusuke; Gache, Vincent; Guyot, Stéphane; Storck, Sébastien; Blanchard-Gutton, Nicolas; Barthélémy, Inès; Walmsley, Gemma; Rahier, Anaëlle; Gadin, Stéphanie; Maurer, Marie; Guillaud, Laurent; et al. (Journal of molecular cell biology, 2015)
The reduced diameter of skeletal myofibres is a hallmark of several congenital myopathies, yet the underlying cellular and molecular mechanisms remain elusive. In this study, we investigate the role of HACD1/PTPLA, which is involved in the elongation of the very long chain fatty acids, in muscle fibre formation. In humans and dogs, HACD1 deficiency leads to a congenital myopathy with fibre size disproportion associated with a generalized muscle weakness. Through analysis of HACD1-deficient Labradors, Hacd1-knockout mice, and Hacd1-deficient myoblasts, we provide evidence that HACD1 promotes myoblast fusion during muscle development and regeneration. We further demonstrate that in normal differentiating myoblasts, expression of the catalytically active HACD1 isoform, which is encoded by a muscle-enriched splice variant, yields decreased lysophosphatidylcholine content, a potent inhibitor of myoblast fusion, and increased concentrations of ≥ C18 and monounsaturated fatty acids of phospholipids. These lipid modifications correlate with a reduction in plasma membrane rigidity. In conclusion, we propose that fusion impairment constitutes a novel, non-exclusive pathological mechanism operating in congenital myopathies and reveal that HACD1 is a key regulator of a lipid-dependent muscle fibre growth mechanism.